GROUP DYNAMICS WITH SPANISH STUDENTS AS A HERITAGE, FOREIGN AND NATIVE LANGUAGE (Živi jezici: Journal for Foreign Languages and Literatures, 2019)
Needs and approaches in teaching native speakers are different than in foreign language teaching, however, as not enough attention has been paid to this area, it is not uncommon for native speakers to learn Spanish in a formal context in mixed groups with foreign speakers, and in some circumstances with native speakers. The research part of this paper consists of the analysis of the questionnaire on learning in mixed groups and the relationship between the mentioned three different groups of students. Hispanic students from three German universities answered the questionnaire, where the groups are extremely mixed due to the large number of Hispanic emigrants in the country. The research was supported by an interview with lecturer T.D. from the Department of Romance Studies at Humboldt University on student work in mixed groups. The results of the research showed that learning in mixed groups has multiple advantages and few limitations for students who are aware of this and would not choose to learn Spanish in common circumstances, different from what they are used to.
Keywords: learners of Spanish as a foreign language; native speakers; Spanish language teaching; teaching in mixed groups; heritage speakers